IMPLEMENTASI SISTEM DIGITAL DALAM PENGELOLAAN KEUANGAN SEKOLAH DASAR DI SD IT MITRA CENDEKIA INDONESIA - Nadroh, Siti; Tissa Puspita; Syahda Rifa; Rohmatul Aliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of digital systems in financial management in elementary schools and their impact on transportation, accuracy, and efficiency of financial administration. The implementation of digital systems, such as budget recording applications, non-cash payments, and online-based reporting, has begun to be used as an effort to modernize school governance. The research method used is a descriptive study with data collection through observation, interviews, and document analysis in several elementary schools. The results show that the use of digital systems can increase the speed of transaction recording, minimize manual errors, and strengthen accountability through more transparent reporting. However, obstacles such as limited human resources, internet access, and technology adaptation remain challenges in its implementation. Overall, digital systems have the potential to be an effective solution to improve the quality of financial management in elementary schools if supported by ongoing training and adequate infrastructure.